Polskie leksemy o rdzeniu piecz-/piek- pochodne od piec się - Krótki, Zuzanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
In this article, the author presents the lexical family with piecz-/piek- roots. A pool of 39 lexemes was extracted from all the available lexicographic sources of historical vocabulary and presented in the form of a word-forming cluster. The goal of the analysis was to display the internal structure of the chronological derivation of the core of the cluster, piec się with the group of terms of varying degrees of derivation. The analysis is an attempt at explaining the meaning behind the formations with piecz-/piek-roots. The reconstruction of the cluster leads to a discussion of the observed transformations, as well as identifying the nature of the changes to the meaning of specific units. To a large extent, the semantic modifications discussed contributed to constraints in the meaning. Once the primary meaning had disappeared, Polish language users would gradually become less aware of the word formation of the derivatives. Subsequently, the very large etymological cluster disintegrated.